PREVALENCE, PATTERN, AND RISK FACTORS FOR URINARY INCONTINENCE AMONG WOMEN IN A LOW-RESOURCE SETTING - Okesina, Bolanle; Fehintola, Akintunde; Raji, Hadijat; Abdur-Rahim, Foyeke; Ajiboye, Akinyosoye; Ayegbusi, Oluwole (Sanamed, 2024)
Introduction: Urinary incontinence (UI) is a common but under-reported condition among women in low-resource settings. The prevalence and pattern of UI, as well as associated risk factors must be examined to inform appropriate health interventions. This study investigated the prevalence, pattern, and risk factors for UI among women in a low-resource setting. Methods: This community-based cross-sectional study was conducted among 400 women ≥ 15 years old in Ilorin South Local Government Area, Kwara State, Nigeria. An interviewer-administered questionnaire was used to collect socio-demographic and health-related data on UI The prevalence of UI was determined using the International Consultation on Incontinence Modular Questionnaire-Urgency Frequency Scale (ICIQ-UFS). Analysis was done using SPSS version 20. Results: The mean age of the respondents was 47.9 (±4.5), and 200 (50.0%) were grand-multipara. The prevalence of UI among women in our study setting was 52.7%. The most common pattern of UI was stress incontinence at 140 (67%), followed by mixed incontinence at 45(21%) and urge incontinence at 26 (12%). Age (p<0.001), parity (p= 0.006), and BMI (p<0.001) were significantly associated with UI. Conclusion: The findings of this study suggest that UI is highly prevalent among our study population and that age, parity, and BMI are associated with the occurrence of UI. There is a need for interventions that focus on preventing and managing UI among women in low-resource settings.